The Economic Consequences of Sovereign International Economic Agreements for Pakistan (Journal of Asian Development Studies, 2026)
This study examines the impact of international economic agreements, specifically trade treaties and tax treaties, on Pakistan’s RGDP from 1975-2023, through fiscal and macroeconomic channels, including tax revenue, FDI Inflow and trade openness. Understanding the role of such agreements is particularly important for developing economies, where policymakers increasingly rely on attracting investment, expanding trade and stimulating economic growth. Evaluating whether these agreements actually deliver the expected economic benefit is therefore essential for designing effective economic and fiscal policies. Using the ARDL model, we find that trade treaties negatively impact trade openness and have an insignificant positive effect on tax revenue, while double tax treaties reduce tax revenue andhave little impact on trade openness. Both agreements, however, significantly boost FDI Inflow. These variables have a negligible direct effect on RGDP. Sobel test results reveal that trade treaties and double tax treaties indirectly influence RGDP through FDI Inflow. Overall, these agreements contribute little to RGDP directly or indirectly. The study recommends that Pakistan restructure the treaty framework to enhance transparency, align incentives with national interests, and ensure public access to relevant data